2014
DOI: 10.7752/jpes.2014.02042
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The aim of this research was to investigate the relation between the psychological well-being and psychological needs of people who participated in recreational dance activities. The sample of the research consisted of 290 adults, aged from 40 to 70 (Μ = 55.6; SD = ± 9.68), who had been taught Greek dances in cultural societies, for an average of 4.5 years (SD = ± 1.2). In order to conduct the study the following instruments were used: a) the Basic Psychological Needs in Exercise Scale (BPNES-Vlachopoulos & Mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…However, in terms of the findings of this article, the qualitative and quantitative data did broadly support one another. It also important to note that the experimental older adults already had relatively high levels of well-being indices at the start of the project, reporting scores that were higher than those in previous studies of older adults in terms of basic need satisfaction (Goulimaris et al, 2014), positive affect (Mather and Knight, 2005;Parker et al, 2008), and social well-being (Keyes, 1998). This may in part explain the lack of significance in change over time.…”
Section: Limitationsmentioning
confidence: 87%
“…However, in terms of the findings of this article, the qualitative and quantitative data did broadly support one another. It also important to note that the experimental older adults already had relatively high levels of well-being indices at the start of the project, reporting scores that were higher than those in previous studies of older adults in terms of basic need satisfaction (Goulimaris et al, 2014), positive affect (Mather and Knight, 2005;Parker et al, 2008), and social well-being (Keyes, 1998). This may in part explain the lack of significance in change over time.…”
Section: Limitationsmentioning
confidence: 87%
“…In the case of dance, this percentage drops slightly due to its characteristics, the use of traditional methodologies (Piéron and Delmelle, 1983), and specifically the levels of satisfaction obtained (Goulimaris, Mavridis, Genti and Rokka, 2014) which can act as determining factors in order to make greater use of this time. The same occurs in this research, since 14.49% of time is employed, which shows an appropriate preparation of music and exercises.…”
Section: Discussionmentioning
confidence: 99%
“…Comparing three age groups, the younger one around 40-50, and the older one around 75, studies have found that the oldest group tend to present higher basic psychological needs fulfillment (Goulimaris, Mavridis, Genti, & Rokka, 2014;Mackenzie, Karaoylas, & Starzyk, 2017), higher well-being and lower stress (Goulimaris et al, 2014). Mackenzie et al (2017) also found the basic psychological needs fulfillment mediates the relationship between motivational constructs and well-being outcomes in all age groups.…”
Section: Basic Psychological Needs Coping and Procrastination In The Context Of Healthy Agingmentioning
confidence: 99%
“…Being involved in academic activities may be a way for adults and older people to improve their basic psychological needs and, as the older students tend to internalize the activities in which they are interested, the academic context should consider these needs satisfaction in order to promote higher levels of psychological well-being. Only when an activity satisfies the personal need for competence, autonomy and relatedness, the activity will be lived as pleasant and the involvement in it will occur for internal reasons (Goulimaris et al, 2014). As age increases, we tend to be more involved in activities as they are able to intrinsically motivate us, and that is why a context that satisfies the psychological needs seems even more relevant for older students.…”
Section: Implications and Conclusionmentioning
confidence: 99%